Simplicity & complexity in Design - Jahanshah Pakzad (صفه)
Although the topic of simplicity and complexity has deep roots in the field of achitectural theory , the discussion about the actual characteristics of these two concepts has yet to be concluded and has still kept its attraction.The present article gives a breif definition of these terms and introduces a system which helps the visual classification of all design pattern in the two categories of simplicity and complexity.